Leaf blade elongation, yield and forage quality in nine grasses under rainfed conditions - Rodríguez-Ortega, Leodan Tadeo; Hernández-Reséndiz, Efraín Jehú; Landa-Salgado, Patricia; Velázquez-Martínez, Mauricio; Hernández-Guzmán, Filogonio Jesús; Ramayo-Ramírez, José Orlando (Ecosistemas y Recursos Agropecuarios, 2025)
In the face of climate change, erratic and heterogeneously distributed rainfall, natural grasslands regain importance as they require less precipitation for forage production. The objective of the study was to evaluate nine mexican grasses under rainfed conditions for forage yield and quality. The study began in march and ended in september 2023 in Tulancingo, Hidalgo. The grasses evaluated were Bouteloua repens, Disakisperma dubium, Bouteloua curtipendula, Bouteloua gracilis, Pappophorum vaginatum, Panicum virgatum, Tripsacum dactyloides, Sporobolus airoides and Pappophorum bicolor. Leaf blade elongation (LBE), yield forage, crude protein (CP), organic matter and in vitro digestibility at 48 h were evaluated. Completely randomized block design and Tukey test (α = 0.05) were used. The LBE was different (P < 0.05), where P. bicolor, T. dactyloides and S. airoides stood out for higher values and longer blades. The highest forage yield was observed in B. curtipendula (P < 0.05; 5 400 kg ha-1), followed by P. vaginatum and T. dactyloides (3 907 and 3 672 kg ha-1, respectively). The highest CP content (P < 0.05) was observed in T. dactyloides (7.48%) and B. repens (7.43%). The highest digestibility was observed in P. virgatum and B. repens with 64.61 and 48.24%, respectively. The grasses B. curtipendula, T. dactyloides, P. bicolor and P. virgatum can be outstanding options for forage use in the face of low rainfall in soils where agriculture is risky